PKM Taman Baca Kampung Pesisir Karabba (Sekolah Sore) - Nur Amalia; Ahmad Subair; La Malihu; Patahuddin Patahuddin (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2022)
The Partner of this Community Partnership Program is a karabba slum community located on the coast of makassar city. The people of karabba slums face various problems amid the rapid urbanization of makassar city. among them in the field of education, namely the low interest and awareness of learning of the karabba slum community in formal education schools, this occurs due to the lack of educational facilities available in karabba slums, as well as the lack of educator resources available in karabba slums. With the karabba slum community partnership program, it is hoped that it will be able to deal with one of the urbanization problems in karabba village, namely increasing the quality of education for the karabba slum community and achieving a common awareness between the karabba village community about the importance of going to school in the midst of the rapid flow of urban urbanization and encouraged by various resources available in the field of education so as to be able to achieve the sustainability of the quality of education karabba slum community.